Comparison of the Incidence, Risk Factors and Types of Acute Rejection between Indigenous and Non-Indigenous Australians with Kidney Transplants. (July 2018) - Howson, Prue; Irish, Ashley; D'Orsogna, Lloyd; Swaminathan, Ramyasuda; Perry, Gregory; Wong, Germaine; Lim, Wai H
Abstract : Introduction: Acute rejection remains a major cause of allograft dysfunction in kidney transplant recipients. Prior research had found a higher incidence of any acute rejection in Indigenous Australians compared to Australians of other descent, but the patterns of this excess risk are not well described. Materials and Methods: Indigenous end-stage kidney disease patients who have received a kidney transplant between 2000-2010 in Western Australia were included. Patient-level data (follow-up censored 31st July 2017) were extracted from the Australian and New Zealand Dialysis and Transplant Registry (ANZDATA) and local databases to determine the rejection rate, risk factors and patterns of acute rejection in indigenous and non-indigenous recipients. Association between ethnicity and rejection was assessed using adjusted Cox regression analysis. Results and Discussion: Of 618 patients who had received a live or deceased donor kidney transplant, 59 (9.5%) were indigenous. Compared to non-indigenous recipients, Indigenous recipients were more likely to have diabetes (37% vs. 13%, p<0.001), had longer mean (SD) waiting time (>5 years: 46% vs. 19%, p<0.001) and were more likely to have received a poorly matched kidney (4-6 HLA-mismatched kidneys: 68% vs. 35%, p<0.001). During a median (IQR) follow up of time of 7.9 (5.7) years, the acute rejection rate for indigenous and non-indigenous recipients was 73 (95%CI 60-83) and 43 (39-47) per 100 recipients (p<0.001). Multiple rejection episodes were significantly greater in indigenous recipients (47 [35-60] vs. 23 [20-27] per 100 recipients; p<0.001). Indigenous recipients were more likely to experience acute rejection compared to non-Indigenous recipients with an adjusted HR of 1.79 (95%CI 1.24, 2.58, p=0.002), independent of HLA-mismatches, donor and recipient age. Greater number of HLA-mismatches and sensitisation status were associated with the occurrence of any rejections, with no interaction between ethnicity and these predictors for rejection. In rejection episodes with a recorded Banff classification (234/283, 83%), indigenous recipients were more likely to experience glomerular (i.e. Banff "g" score of ≥1; 39.5% vs 24% non-Indigenous, p=0.048) and antibody-mediated rejection (i.e. Banff ptc≥1±C4d≥1 or C4d≥2; 39.5% vs 19.9% non-Indigenous, p=0.009), compared to non-indigenous recipients. Median (IQR) time to first acute rejection episodes was not significantly different between indigenous and non-indigenous recipients (6.4 [1.9-25.7] vs. 3.6 [0.5-20.7] months, p=0.492). Conclusions: Over 70% of indigenous kidney transplant recipients experienced acute rejection after transplantation, with almost 40% of rejections attributed to AMR. Understanding the reasons for the disparity in acute rejection between indigenous and non-indigenous recipients is crucial in improving allograft outcomes in this population.